Integrating Free-Range Hens into a Regenerated Medic Pasture - Glatz, P.C.; Ru, Y.J.; Miao, Z. H.; Wyatt, S.K.; Rodda, B.J. (International Journal of Poultry Science, 2005)
In Australia some grain farmers, market gardeners and graziers integrate hens into their farming system. In this system, hens are unrestricted in their movements except that they are usually locked in sheds at night for protection from predators. Consumers pay a premium for eggs and chicken meat on the grounds of enhanced welfare of hens in this system. The purpose of this experiment was to determine the impact of hens integrated into a regenerated medic pasture on pasture availability, prevalence of weeds and soil fertility before and after grazing. Sheep were used as a comparison in the experiment. Laying hens stocked at 110/ha (compared to sheep-stocking density 12/ha) foraged on a regenerated medic pasture for 16 weeks. Egg production of 67.8% for free-range hens at week 60 was lower compared to the industry cage standard (83.0% at the same age). However, the live weight of free-range hens (2.3kg) was higher than the cage standard (2.0kg). Herbage availability in hen paddocks after grazing was considerably higher (P< 0.05) than in sheep paddocks. Hens ingested less (P< 0.05) barley grass (2.6 vs. 0.3 no./0.1m2) and other grass (4.2 vs. 0.5 no./0.1m2) compared to sheep. Paddock soil nitrate nitrogen was lower (P< 0.05) for both hens (30.7 before grazing vs. 0.4 mg/L after grazing) and sheep (28.2 before grazing vs. 1.2 mg/L after grazing). The penetrometer readings were significantly increased (p< 0.01) in sheep paddocks (3.9 before grazing to 9.1 after grazing) and in hen paddocks (P< 0.05) (3.0 before grazing to 4.8 after grazing).